2022
DOI: 10.3389/fendo.2022.1032323
|View full text |Cite
|
Sign up to set email alerts
|

Association between body fat distribution and kidney stones: Evidence from a US population

Abstract: ObjectivesWe aimed to evaluate the relationship between the proportion of Android to Gynoid ratio and the incidence of kidney stones among US adults.MethodsParticipants aged 20-59 years from the 2011-2018 National Health and Nutrition Examination Survey (NHANES) database were selected to assess the association between Android to Gynoid ratio and kidney stone prevalence using logistic regression analysis, subgroup analysis and calculation of dose-response curves.ResultsThis study ultimately included 10858 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…A recent study found that small height was associated with stone formation but not weight ( 28 ), which may be due to the limitations of BMI ( 29 ) and the presence of the obesity paradox ( 22 ). In order to better explore the relationship between obesity and kidney stones, some recent studies tend to use non-traditional obesity indicators as a measure of obesity, such as visceral adiposity index ( 30 ), android-to-gynoid ratio ( 31 ), and so on. To the best of our knowledge, this is the first cross-sectional human study to evaluate the association between WWI and kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that small height was associated with stone formation but not weight ( 28 ), which may be due to the limitations of BMI ( 29 ) and the presence of the obesity paradox ( 22 ). In order to better explore the relationship between obesity and kidney stones, some recent studies tend to use non-traditional obesity indicators as a measure of obesity, such as visceral adiposity index ( 30 ), android-to-gynoid ratio ( 31 ), and so on. To the best of our knowledge, this is the first cross-sectional human study to evaluate the association between WWI and kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicated that the association between risk factors for uric acid stone formation and total body fat and trunk fat was stronger compared to body weight ( 27 ). The Android region, which includes the liver, pancreas, and kidneys, has been linked to an increased incidence of kidney stones, and an increase in the A/G ratio denotes an increase in the fat content of the Android region ( 21 ). On the other hand, Abufaraj et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney stone occurrence (variable name: KIQ 026) was designed as an outcome variable. The participant was considered to have a kidney stone if he or she answered yes to the question, “Have you or the sample person (SP) ever had a kidney stone?” Previous research has established the reliability of self-reported kidney stone status ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid metabolism, including lipoprotein, TC, TG and other indicators, has always been a factor of concern in the risk of urinary calculi [5,[12][13][14] . In this single-center cross-sectional study involving 414 adults, we found that lipid metabolism was closely related to urinary calculi, and higher TyG index was independently related to the occurrence, load and recurrence of kidney calculi.…”
Section: Discussionmentioning
confidence: 99%